Functional outcome assessment for surgical decompression of cervical spondylotic myelopathy - Abraham, Tinu Ravi; John, Ajax; Balakrishnan, P. K.; Jose, Tom (International Surgery Journal, 2021)
Background: Cervical spondylotic myelopathy (CSM) is one of the most common dysfunctions of spinal cord occurs due to degenerative changes in cervical spine disc and facet joints. It is a form of progressive spine disease including herniated disc and spinal cord stenosis which manifests as changes in gait, skilled hand movements, muscle strength, bladder dysfunction etc. Recent studies and trials have established that surgical decompression of cervical spinal is a cost-effective treatment modality which provide satisfactory functional recovery. This study aimed at the functional outcome of surgical decompression of CSM. Methods: The prospective study of 100 cases of cervical myelopathy for which decompressive surgery was done from August 2020 to August 2021. Results were analysed according to Nuricks and modified Japanese orthopedic association scoring system (MJOA). Results: Seventy one males and 29 females were included in this study with average age was 53 and average hospital stay was 3.55 days. Average pre-op Nurick score was 1.93, while score after 6 months and 1year were 1.44 and 1.15respectively. Average pre-op MJOA score was 13.63, while score after 6 months and 1 year were 14.58 and 15.74 respectively. Conclusions: The functional results of decompressive surgeries for cervical myelopathy are satisfactory. Both anterior and posterior approaches are recommended for multiple cervical myelopathy with comparable outcomes. DM and age was observed as the independent predictor for functional outcome, while, gender and level of disease got less significant predictive value.